2022
DOI: 10.1002/jmv.27898
|View full text |Cite
|
Sign up to set email alerts
|

Performance of nasopharyngeal swab and saliva in detecting Delta and Omicron SARS‐CoV‐2 variants

Abstract: A prospective cohort study was conducted during the Delta and Omicron severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) epidemic waves from paired nasopharyngeal swab (NPS or NP swab) and saliva samples taken from 624 participants.The study aimed to assess if any differences among participants from both waves could be observed and if any difference in molecular diagnostic performance could be observed among the two sample types. Samples were transported immediately to the laboratory to ensure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
7
16
1
Order By: Relevance
“…This is consistent with the technical report of the European Centre for Disease Prevention and Control, which states that the suitability of saliva sampling for rapid antigen tests is not supported by the available data and that nasopharyngeal sampling remains the gold standard [26]. Saliva sample type also had low sensitivity in some clinical and analytical studies [1,2], and the average viral load in saliva was reported to be lower than for nasopharyngeal swabs [27].…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with the technical report of the European Centre for Disease Prevention and Control, which states that the suitability of saliva sampling for rapid antigen tests is not supported by the available data and that nasopharyngeal sampling remains the gold standard [26]. Saliva sample type also had low sensitivity in some clinical and analytical studies [1,2], and the average viral load in saliva was reported to be lower than for nasopharyngeal swabs [27].…”
Section: Discussionsupporting
confidence: 79%
“…[47] Therefore, we did not assess the performance of saliva testing in presence of more transmissible but milder variants. [48] However, saliva testing performance seems similar in the presence of Delta and Omicron SARS-CoV-2 variants. In spite of the potential usefulness of saliva tests, our findings cannot be directly extrapolated to other populations.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we observed reduced clinical diagnostic sensitivity of saliva collected by buccal swabs in comparison to matched combined oro-/nasopharyngeal swabs in the detection of Omicron (BA.1 and BA.2). Serval studies on the sensitivity of saliva versus respiratory tract specimens for the detection of SARS-CoV-2, including Omicron, have been conducted, leading to mixed and in parts contradictory results [5][6][7][8][11][12][13]. In this study, samples were collected from hospitalized, symptomatic individuals who had previously been confirmed to be SARS-CoV-2 positive, resulting in sample collection at median six days after initial symptom onset.…”
Section: Discussionmentioning
confidence: 99%